Predictive value of neutrophil gelatinase-associated lipocalin in children with acute kidney injury: A systematic review and meta-analysis - Zou, Zhuan; Chen, Bin; Tang, Fajuan; Li, Xihong; Xiao, Dongqiong (Frontiers in Pediatrics, 2023)
Purpose: Neutrophil gelatin lipase carrier protein (NGAL) has been used as an early biomarker to predict acute kidney injury (AKI). However, the predictive value of NGAL in urine and blood in children with acute kidney injury in different backgrounds remains unclear. Therefore, we conducted this systematic review and meta-analysis to explore the clinical value of NGAL in predicting AKI in children. Methods: Computerized databases were searched for relevant the studies published through August 4th, 2022, which included PUBMED, EMBASE, COCHRANE and Web of science. The risk of bias of the original included studies was assessed by using the Quality Assessment of Studies for Diagnostic Accuracy (QUADA-2). At the same time, subgroup analysis of these data was carried out. Results: Fifty-three studies were included in this meta-analysis, involving 5,049 patients, 1,861 of whom were AKI patients. The sensitivity and specificity of blood NGAL for predicting AKI were 0.79 (95%CI: 0.69-0.86) and 0.85 (95%CI: 0.75-0.91), respectively, and SROC was 0.89 (95%CI: 0.86-0.91). The sensitivity and specificity of urine NGAL for predicting AKI were 0.83 (95%CI: 0.78-0.87) and 0.81 (95%CI: 0.77-0.85), respectively, and SROC was 0.89 (95%CI: 0.86-0.91). Meanwhile, the sensitivity and specificity of overall NGAL (urine and blood NGAL) for predicting AKI in children were 0.82 (95%CI: 0.77-0.86) and 0.82 (95%CI: 0.78-0.86), respectively, and SROC was 0.89 (95%CI: 0.86-0.91). Conclusion: NGAL is a valuable predictor for AKI in children under different backgrounds. There is no significant difference in the prediction accuracy between urine NGAL and blood NGAL, and there is also no significant difference in different measurement methods of NGAL. Hence, NGAL is a non-invasive option in clinical practice. Based on the current evidence, the accuracy of NGAL measurement is the best at 2 hours after cardiopulmonary bypass (CPB) and 24 hours after birth in asphyxiated newborns.